More Effectiveness in Blended Learning - Mohammad, Ali Molaei (INTI International University, 2007)
Online education is likely to continue to grow in popularity in the years ahead, and both schools and universities are expected to take an especially strong interest in “Online” courses. And it’s necessary to know the level of student success and retention. Recent studies comparing student performance, satisfaction, and persistence between online and face to face classes course found no significant difference in grades between online and traditional classes; however, students in the online course were significantly less satisfied with the course on several dimensions. Among the most often cited are physical isolation, lack of social support or interaction, and high attrition rates. The intent of this study was to examine differences (quality & satisfaction) between online and traditional classroom learning for undergraduate course and to highlight the effectiveness of blended-style education. Specifically, the study explores the difference between three methods of learning (E-learning, face to face and blended-style of education) which is measured by final course grades and student satisfaction which is measured by student evaluation of instruction ratings. Moreover the article explores the concept and benefits of blended learning through the review of literature.